2018
DOI: 10.1177/0011128718811927
|View full text |Cite
|
Sign up to set email alerts
|

A Near Repeat Examination of Economic Crimes

Abstract: Criminological inquiry has recently showcased increased attention toward the near repeat phenomenon, which suggests that following an initial criminal event, there is an increased risk for the occurrence of the same type of event spatially and temporally proximate to the initiating event. The majority of previous research tends focuses on the patterns related to violent and conventional property crimes but neglects to examine other economic-related crimes. Given the significant costs associated with this crime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Spatio-temporal patterns of arson reveal a higher amount of incidents occurring at night, over the weekend, and in areas with little surveillance (Asgary et al 2010;Grubb and Nobles, 2016;Potter 2000). Arson also demonstrates near-repeat clustering (Grubb and Nobles 2016;Turchan et al 2018) typically observed within other crime types (Bernasco 2008;Johnson 2008;Townsley et al 2003;Powell et al 2019).…”
Section: Crime As Rational Opportunitymentioning
confidence: 75%
“…Spatio-temporal patterns of arson reveal a higher amount of incidents occurring at night, over the weekend, and in areas with little surveillance (Asgary et al 2010;Grubb and Nobles, 2016;Potter 2000). Arson also demonstrates near-repeat clustering (Grubb and Nobles 2016;Turchan et al 2018) typically observed within other crime types (Bernasco 2008;Johnson 2008;Townsley et al 2003;Powell et al 2019).…”
Section: Crime As Rational Opportunitymentioning
confidence: 75%
“…While most work on near repeat crime patterns has been focused on burglary (S. D. Johnson et al, 2007; Townsley et al, 2003), it has been shown to extend to a variety of different crime types: robbery, shootings, theft from motor vehicles, thefts of motor vehicles, arson, assault, economic crimes, piracy, and terroristic events (Behlendorf et al, 2012; Block & Fujita, 2013; Braithwaite & Johnson, 2012; Haberman & Ratcliffe, 2012; Lockwood, 2012; Marchione & Johnson, 2013; Powell et al, 2019; Sturup et al, 2018; Townsley et al, 2008; Turchan et al, 2019; Wells et al, 2012; Youstin et al, 2011; Zhang et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a house is burglarized on a Monday, and the next door neighbor is burglarized the following Wednesday. While most work on near repeat crime patterns has been focused on burglary (Townsley, Homel, & Chaseling, 2003;Johnson et al, 2007), it has been shown to extend to a variety of different crime types: robbery, shootings, theft from motor vehicles, thefts of motor vehicles, arson, assault, economic crimes, piracy, and terroristic events (Behlendorf, LaFree, & Legault, 2012;Block & Fujita, 2013;Braithwaite & Johnson, 2012;Haberman & Ratcliffe, 2012;Marchione & Johnson, 2013;Powell, Grubb, & Nobles, 2018;Sturup et al, 2018;Townsley, Johnson, & Ratcliffe, 2008;Turchan et al, 2018;Wells, Wu, & Ye, 2012;Youstin et al, 2011;Zhang et al, 2015).…”
Section: Overview Of Near Repeat Crime Patternsmentioning
confidence: 99%